Validity and reliability of the adapted Malay version of the parenting and child toothbrushing assessment (M-PACTA) for children with attentiondeficit hyperactivity disorder in a medical centre- A pilot study / Gowry Paramasivam - Gowry , Paramasivam (2024)
Attention-Deficit Hyperactivity Disorder (ADHD) poses unique challenges for children and their parents, impacting various aspects of daily life, including the establishment of consistent oral hygiene practices. Given the complexity of managing ADHD-related behaviours, effective assessment tools are needed to evaluate parental experiences and child behaviours related to toothbrushing. This study aimed to assess the validity and reliability of the M-PACTA in evaluating behaviours of children with ADHD, along with parental strategies, knowledge, and attitudes regarding toothbrushing. The 77-item MPACTA questionnaire was adapted to the context of children with ADHD through a twophase process. Phase I focused on content and face validity, where five specialists from various departments reviewed the questionnaire to ensure its relevance and clarity. This was followed by cognitive debriefing with ten parents of children with ADHD to evaluate the readability, formatting, and language clarity of the revised questionnaire. Phase II encompassed comprehensive psychometric assessments, including detailed analyses of construct validity and reliability. The study recruited 42 parents of children aged 6-12 years diagnosed with ADHD, who were receiving care at Departments of Paediatrics and Psychiatry, Universiti Malaya Medical Centre (UMMC) from March to June 2024, using universal sampling. Expert evaluation showed excellent content and face validity for relevance and clarity, with CVI scores from 0.75 to 1.00 and Kappa values from 0.72 to 1.00, except for five items. One item was deleted due to low relevance, and four items were modified for clarity based on experts' recommendations. Exploratory factor analysis identified distinct factor structures for the four scales: Child Behaviour (two factors), Parental Strategies (five factors), Parental Attitude (four factors), and Parental Knowledge (two factors). Five items were dropped due to cross-loadings, negative loadings, and no loadings. Reliability analysis showed moderate to strong internal consistency (Cronbach's alpha 0.616 to 0.938) and test-retest reliability (ICC values 0.657 to 0.957). The final questionnaire had 71 items, specifically tailored for ADHD children. In conclusion, the adapted M-PACTA for children with ADHD demonstrated satisfactory construct validity and reliability in assessing children's behaviours, parental strategies, knowledge, and attitudes towards toothbrushing among children with ADHD at UMMC.